2017
DOI: 10.1128/jb.00802-16
|View full text |Cite
|
Sign up to set email alerts
|

ArtA-Dependent Processing of a Tat Substrate Containing a Conserved Tripartite Structure That Is Not Localized at the C Terminus

Abstract: Most prokaryote-secreted proteins are transported to the cell surface using either the general secretion (Sec) or twin-arginine translocation (Tat) pathway. A majority of secreted proteins are anchored to the cell surface, while the remainder are released into the extracellular environment. The anchored surface proteins play a variety of important roles in cellular processes, ranging from facilitating interactions between cells to maintaining cell stability. The extensively studied S-layer glycoprotein (SLG) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…We have recently been able to directly demonstrate ArtA‐dependent processing of a PGF tripartite structure containing protein, Hvo_0405. As the PGF tripartite structure of this H. volcanii ArtA substrate is located toward the center of the protein, rather than near the C‐terminus, it is an ideal reporter protein for studies on ArtA processing since the processed N‐ and C‐terminal proteins derived from Hvo_0405 can be readily observed on an LDS‐PAGE gel (Abdul Halim et al ., ). While the conditions under which chromosomal hvo_0405 is expressed are not yet known, to demonstrate ArtA‐dependent processing of this protein, we have expressed His‐tagged Hvo_0405 in trans under the control of the tryptophanase promoter (p. tnaA ) from the plasmid pTA963, and used antibodies against the N‐terminus of Hvo_0405His and the C‐terminal His‐tag to detect the processed proteins in immunoblot analyses.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…We have recently been able to directly demonstrate ArtA‐dependent processing of a PGF tripartite structure containing protein, Hvo_0405. As the PGF tripartite structure of this H. volcanii ArtA substrate is located toward the center of the protein, rather than near the C‐terminus, it is an ideal reporter protein for studies on ArtA processing since the processed N‐ and C‐terminal proteins derived from Hvo_0405 can be readily observed on an LDS‐PAGE gel (Abdul Halim et al ., ). While the conditions under which chromosomal hvo_0405 is expressed are not yet known, to demonstrate ArtA‐dependent processing of this protein, we have expressed His‐tagged Hvo_0405 in trans under the control of the tryptophanase promoter (p. tnaA ) from the plasmid pTA963, and used antibodies against the N‐terminus of Hvo_0405His and the C‐terminal His‐tag to detect the processed proteins in immunoblot analyses.…”
Section: Resultsmentioning
confidence: 97%
“…While the conditions under which chromosomal hvo_0405 is expressed are not yet known, to demonstrate ArtA‐dependent processing of this protein, we have expressed His‐tagged Hvo_0405 in trans under the control of the tryptophanase promoter (p. tnaA ) from the plasmid pTA963, and used antibodies against the N‐terminus of Hvo_0405His and the C‐terminal His‐tag to detect the processed proteins in immunoblot analyses. Our results showed that Hvo_0405 can indeed be effectively used as a reporter substrate in studies of ArtA‐dependent processing (Abdul Halim et al ., ). Thus, we sought to determine whether the ArtA‐GFP replacement mutants can cleave this ArtA substrate.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, a novel mechanism was discovered whereby proteins are anchored to the membrane through a lipid moiety covalently attached to a processed C terminus. In archaeal cells, processing and lipid modification of these C-terminal anchored proteins are mediated by enzymes known as archaeosortases, with archaeosortase A (ArtA) of the model archaeon Haloferax volcanii being the most studied example (10)(11)(12)(13). Proteins recognized and processed by H. volcanii ArtA contain a distinct C-terminal tripartite structure consisting of a conserved PGF motif, followed by a hydrophobic domain and then a stretch of positively charged residues.…”
mentioning
confidence: 99%